RESEARCHES REGARDING THE INFLUENCE OF RECOVERY MEDIA ON THE IN VITRO DEVELOPMENT CAPACITY OF THE PREIMPLANTATIONAL MOUSE EMBRYO - ADA CEAN; N. PĂCALĂ; ALEXANDRA BOLEMAN (Scientific Papers Animal Science and Biotechnologies, 2023)
Phosphate Bufered Saline with 0.4% BSA and M2 medium are one of the most common media used in embryo recovery. The aim of our paper was to investigate if the recovery media used for the recovery of the mouse embryo is influencing in vitro developmental capacity. As biological material we used 10 used were mouse females, age 2 months superovulated with 5UI PMSG (Pregnant Mare Serum Gonadotropine) and 5 UI hCG (human Corionic Gonadotropine). The embryos used were recovered, by oviduct flushing, at 24 hours from the identification of the vaginal plug. The majority of the embryos (78.3%) were in two cells stage. A total of 123, 2 cells embryos were cultivated in M16 medium. The evolution of the embryos was examined at 24, 48 and 72 hours interval. The proportion of hatched blastocyst was higher at the embryos recovered with M2 (53.7%) compared with the embryos recovered with PBS 0.4% BSA. The difference is statistically very significant (p<0.001). Embryos recovered in M2 media have a higher in vitro developmental capacity compared with the embryos recovered in PBS media supplemented with 0,4% BSA, possibly because of the sodium bicarbonate and lactate used in M2 media for pH regulation.